ASSESSMENT OF THE FINANCIAL POTENTIAL OF TOURISM AND HOSPITALITY ENTERPRISES IN THE CONTEXT OF STRATEGIC DEVELOPMENT - SAIGAK, Elizaveta (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Established the role and significance of the financial condition assessment in the strategic context of the enterprise's development. Determined the nature of the occurrence is determined and the characteristics of the connection and interdependence of the strategic financial analysis and the strategy formation for the enterprise financial potential development determined. Summarized provisions on determining the content of the company's financial strategy. Defined the main approaches to establishing the financial strategy essence are: the functional-management approach (the planned sequence of actions, i.e., the implementation of the function regarding the accumulation, distribution, use and reproduction of financial resources); the capital approach (proceeds from the imperative nature recognition of the economic entity market value priority in the strategic development of goal systems; assumes a corresponding increase in the financial strategy importance relative to other functional and operational strategies); behavioral approach (based on the assignment to the scope of the financial strategy implementation, first of all, of the principle guidelines for the enterprise's financial relations implementation with other participants in the market interaction). Summarized the financial strategy characteristic properties composition in the mechanism of formation and implementation of other elements strategic set is: a long time of implementation orientation; purposefulness, which determines the orientation and subordination of a financial goals set to the company's fulfilling imperative plans;  the financial goals inclusion in the strategic development implementation mechanism priorities; the functional combination optimality and cost parameters implementation of strategic plan individual elements. Proposed a methodical approach to assessing the enterprise financial potential in the tourism industry and the hospitality field. The financial potential components of the enterprise assessment in the tourism industry and the field of hospitality have been established: the parameters of the enterprise's financial condition; strategic competences in the field of financial management; weighted cost of raising capital.
Keywords: finance; financial potential; financial support; financial strategy; strategic competences; financial condition; tourism industry; hospitality industry